Meta-Analysis: Effect of Bullying on the Risk of Suicide in Adolescents - Aprilia, Sholikha Dela; Prasetya, Hanung; Murti, Bhisma (Journal of Maternal and Child Health, 2023)
Background: Mental health disorders are among the most important public health problems globally. Bullying affects the lives of many children and young people. Studies in high-income countries have reported an association between bullying and suicidal behavior among school adolescents. For example, studies in various parts of the United States found that students who were bullied were significantly more likely to experience suicidal ideation, planning, and suicide attempts. This study aims to determine the effect of bullying on the risk of suicide in adolescents Subjects and Method: The meta-analysis was carried out according to the PRISMA flow chart and the PICO model. Q: Adolescent, I: Bullying , C: Not bullying, O: Risk of suicide. Search for articles in this study through databases that include PubMed, Google Scholar, Science Direct and Scopus. With keywords including: "bullying" AND "suicide" AND "adolescent". A full paper article with a cross-sectional study, the research subjects were adolescents, the relationship size used was the adjusted odds ratio, the research outcome was suicide risk. Analysis done with Revman 5.3 Results:A total of 11 articles with a cross sectional design from Israel, China, Vietnam, Tanzania, Canada, the United States, Iran and South Korea totaling 124,728 research samples. The results showed that adolescents who were bullied had a risk of suicide 2.70 times compared to those who did not experience bullying (aOR=2.70; 95% CI=1.88 to 3.87; p<0.001). Conclusion: Bullying can increase the risk of suicide in adolescents.